Efforts to Increase Academic Resilience of IAIN Syekh Nurjati Cirebon Students Through Strengthening Self-Regulation Capabilities - Gumiandari, Septi; Ulya, Himayatul (Darussalam: Journal of Psychology and Educational, 2023)
In an educational environment, encountering difficulties and challenges is natural. Someone who is able to adapt and overcome these difficulties and challenges means that he has academic resilience abilities. Academic resilience can be increased by using self-regulation abilities. This study aims to determine: (1) students' academic resilience abilities; (2) students' self-regulation abilities; (3) The efforts of IAIN Syekh Nurjati Cirebon students in increasing academic resilience through strengthening their self-regulation abilities. This study uses a qualitative method. The data collection technique used in this research is using interviews. The results of this study reveal that the majority of students have a fairly high level of academic resilience. They say that they will fight the panic and fear of the difficulties and failures that come their way. Even when faced with difficult assignments, they feel challenged and motivated.